(untitled) (Czech Journal of International Relations, 1998)
Michael Bratton, Nicolas van de Walle: Democratic Experiments in Africa: Regime transition in comparative perspective. Cambridge University Press, Cambridge 1997, 307 stran, ISBN 0-521 55429-2.